2014
DOI: 10.1590/1516-3180.2014.1326725
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of celiac disease in patients with autoimmune thyroiditis: cross-sectional study

Abstract: CONTEXT AND OBJECTIVE: Celiac disease is an autoimmune disorder with an average prevalence of 1% in Europe and the United States. Because of strong European ancestry in southern Brazil, this study aimed to evaluate the seroprevalence of celiac disease among autoimmune thyroiditis patients. DESIGN AND SETTING: Cross-sectional study in a public university hospital. METHODS:This cross-sectional prevalence study included autoimmune thyroiditis patients who were tested for anti-endomysial and anti-transglutaminase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Twenty-seven relevant studies were identified, including 6024 individuals with ATD. Six of these studies had screened <100 patients with ATD (9,11,23,24,32,37). The prevalence of CD ranged between 0% and 10% ( Table 1).…”
Section: Background Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-seven relevant studies were identified, including 6024 individuals with ATD. Six of these studies had screened <100 patients with ATD (9,11,23,24,32,37). The prevalence of CD ranged between 0% and 10% ( Table 1).…”
Section: Background Datamentioning
confidence: 99%
“…Type of ATD. The prevalence of CD was slightly higher in hyperthyroidism (2.6% [CI 0.7-4.4]) (11,39,42) (8,23,25,26,28,30,31,33,39,43). The highest pooled prevalence was, however, seen in one study where the age of participants was unclear (9.0% [CI 5.3-12.8%]) (32).…”
Section: Prevalence Of CD In Atd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vigorous CD4 + T-helper 1 cell activation has been implicated in patients with CD (3,4). The association of CD with autoimmune rheumatologic diseases such as juvenile idiopathic arthritis (JIA), rheumatoid arthritis (RA), and primary Sjögren syndrome has been reported (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%